Формування парламенту України: до пошуку оптимальної виборчої системи - Баймуратов, М.О.; Сліденко, І.Д. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
In the article the state and perspective development of electoral legislation is analysed one lected of folk deputies of Ukraine, different approaches are analysed for the choice of the optimum electoral system for forming of parliament of Ukraine.